Theories of democracy : a critical introduction - Cunningham, Frank, 1940- (Routledge contemporary political philosophy., 2002)
This is the first book in this new series on political philosophy. Providing a critical and clear assessment of the main approaches. It discusses the main themes in democratic theory giving concrete examples of their application.